1986
DOI: 10.1021/jf00069a008
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of developing soybeans

Abstract: Fatty acid composition and total free fatty acid content of seven soybean [Glycine max (L.) Merr.] cultivars at various stages of bean development from the 45th day after flowering up to the 75th day, at 10-day intervals, were determined. In almost all the cultivars amounts of palmitic, stearic, and oleic acids and total free fatty acids decreased while those of linoleic and linolenic acids increased during seed maturation. Minor variability in the pattern of these components in different cultivars of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Unfortunately, there is no available literature reporting fatty acid composition of mixed beverages containing fruit juices and soymilk at present. Nevertheless, similar to our results, different authors reported that the main fatty acids in soy beans and soy derivatives are linoleic, oleic, linolenic, stearic and palmitic acids (Peñalvo et al, 2004;Préstamo & Fontecha, 2007;Sangwan, Gupta, & Dhindsa, 1986). Additionally, Peñalvo et al (2004) detected mystiric, palmitoleic, margaric, arachidic, behenic and lignoceric acids in soymilk.…”
Section: Fatty Acid Compoundssupporting
confidence: 91%
“…Unfortunately, there is no available literature reporting fatty acid composition of mixed beverages containing fruit juices and soymilk at present. Nevertheless, similar to our results, different authors reported that the main fatty acids in soy beans and soy derivatives are linoleic, oleic, linolenic, stearic and palmitic acids (Peñalvo et al, 2004;Préstamo & Fontecha, 2007;Sangwan, Gupta, & Dhindsa, 1986). Additionally, Peñalvo et al (2004) detected mystiric, palmitoleic, margaric, arachidic, behenic and lignoceric acids in soymilk.…”
Section: Fatty Acid Compoundssupporting
confidence: 91%
“…In this study, LAB8014 could have produced fatty acids by using the lipid fraction of the soybean drink or of spirulina biomass, boosting the lipid content in the broths at the end of fermentation. Considering that A. platensis F&M-C256 biomass contains LA (1.15%) (Niccolai et al, 2019c) and that the most abundant fatty acid in soybean is LA (Sangwan et al, 1986), it is probable that during fermentation bacteria converted LA to CLA further improving the beneficial properties of the fermented broths. In the case of SD broth, without bacterial inoculation, the presence of LAB8014 after 48 h of fermentation could have lead to the same phenomena.…”
Section: Nutritional Composition and In Vitro Digestibility Of Lyophimentioning
confidence: 99%
“…Fatty acids (FA) are distributed between 15% saturated and 80% unsaturated. The most abundant FA in soybeans is linoleic acid (C18:2 n-6) representing approximately half of the total content, although it also contains considerable levels of the other essential FA, i.e., linolenic acid (C18:3 n-3) [1,2]. Humans are capable of converting linoleic acid to arachidonic acid (C20:4 n-6), and to a lesser extent, linolenic acid to eicosapentanoic (C20:5 n3) and docosahexanoic (C22:6 n-3) acids.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its optimal nutritional profile and resemblance to dairy milk, it can be used as an animal milk complement or substitute, in cases of lactose intolerance. Soybean FA distribution has been studied to some extent [2] but no investigations have been carried out on the effect that the elaboration conditions may exert on the final FA profile of soymilk. Traditional soymilk extraction implies a soaking step followed by a thermal treatment for 1.5 h [5].…”
Section: Introductionmentioning
confidence: 99%